Upper and lower solutions method for impulsive differential equations involving the Caputo fractional derivative - Hamani, Samira; Benchohra, Mouffak; RP, Agarwal; Pinelas, S (Memoirs on Differential Equations and Mathematical Physics, 2011)
For impulsive differential equations involving the Caputo fractional derivative, sufficient conditions for the solvability of initial value problem are established using the lower and upper solutions method and Schauder’s fixed point theorem.
Keywords: Initial value problem, fractional differential equations, impulses, Caputo fractional derivative, fractional integral, lower and upper solution, fixed point.